Strategi Revitalisasi Pelajaran PAI untuk Membangun Harmoni Antarumat Beragama di Maluku - Asbarin; Nabila Nailil Amalia; Husnaini Jamil (ASSUNNAH PRESS, 2025)
Islamic Religious Education (PAI) has a strategic role in shaping the character of tolerant students in the midst of a diverse society. However, in Maluku, the implementation of tolerance values in PAI has not been fully effective, as can be seen from the conflicts between students that are still occurring. This research aims to formulate a PAI revitalization strategy based on Pela Gandong local wisdom and a multicultural approach to build harmony between religious communities. The research uses a descriptive qualitative method with a multisite approach, involving three State Aliyah Madrasah (MAN) in Maluku. Data were obtained through in-depth interviews, observations, and documentation studies, then analyzed using thematic techniques. The results showed that the integration of Pela Gandong values in PAI learning increased students' awareness of tolerance, with most of the student and teacher respondents stating positive changes. The multicultural approach creates more inclusive cross-cultural interactions, despite the constraints of lack of teacher training and resistance to curriculum change. These findings emphasize the importance of supporting traditional, religious, and school policy leaders for successful implementation. This study concludes that PAI revitalization based on Pela Gandong and multiculturalism is an effective strategy to build a more tolerant society in Maluku.